Pinched hysteresis scaling in hybrid-doped BaTiO3 - Sukrit Sucharitakul (2018)
In order to investigate the mechanism of hybrid doped ferroelectric, BaTiO3 sample was prepared via conventional mixed-oxide method. The sample was then subjected to doping process with Fe3+ as acceptor dopant and Nb5+ as donor dopant. With varied concentration of acceptor dopant from 0.5 to 1 %M at fixed 1%M of donor, hysteresis property was obtained via Sawyer-Tower circuit. The hysteresis property of the sample was observed to vary over time by influence of ageing effect. By numerical scaling, the stretched exponential decay behavior of the system was obtained to gain the better insight of ageing mechanism of hybrid doped ferroelectric. With stretched exponential fitting, stretching parameter of lower doped Nb5+ were observed lower than that of equivalently doped Nb5+. © (2010) Trans Tech Publications.